Scientific Opinion on the substantiation of health claims related to a combination of Lactobacillus rhamnosus CNCM I‐1720 and Lactobacillus helveticus CNCM I‐1722 and defence against pathogenic gastro‐intestinal microorganisms (ID 939, further assessment) pursuant to Article 13(1) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a health claim related to a combination of Lactobacillus rhamnosus CNCM I‐1720 and Lactobacillus helveticus CNCM I‐1722 and defence against pathogenic gastro‐intestinal microorganisms. The food constituent that is the subject of the health claim, a combination of Lactobacillus rhamnosus CNCM I‐1720 and Lactobacillus helveticus CNCM I‐1722, is sufficiently characterised. The claimed effect, defence against pathogenic gastro‐intestinal microorganisms, is a beneficial physiological effect. The proposed target population is the general population. No human intervention studies were provided from which conclusions could be drawn for the scientific substantiation of the claim. On the basis of the data provided, the Panel concludes that a cause and effect relationship has not been established between the consumption of a combination of Lactobacillus rhamnosus CNCM I‐1720 and Lactobacillus helveticus CNCM I‐1722 and defence against pathogenic gastro‐intestinal microorganisms.